Heterogeneity and Remodeling of Ion Currents in Cultured Right Atrial Fibroblasts From Patients With Sinus Rhythm or Atrial Fibrillation - Jakob, Dorothee; Klesen, Alexander; Darkow, Elisa; Kari, Fabian A.; Beyersdorf, Friedhelm; Kohl, Peter; Ravens, Ursula; Peyronnet, Rémi (Frontiers in Physiology, 2021)
Cardiac fibroblasts express multiple voltage-dependent ion channels. Even though fibroblasts do not generate action potentials, they may influence cardiac electrophysiology by electrical coupling via gap junctions with cardiomyocytes, and through fibrosis. Here, we investigate the electrophysiological phenotype of cultured fibroblasts from right atrial appendage tissue of patients with sinus rhythm (SR) or atrial fibrillation (AF). Using the patch-clamp technique in whole-cell mode, we observed steady-state outward currents exhibiting either no rectification or inward and/or outward rectification. The distributions of current patterns between fibroblasts from SR and AF patients were not significantly different. In response to depolarizing voltage pulses, we measured transient outward currents with fast and slow activation kinetics, an outward background current, and an inward current with a potential-dependence resembling that of L-type Ca2+ channels. In cell-attached patch-clamp mode, large amplitude, paxilline-sensitive single channel openings were found in ≈65% of SR and ∼38% of AF fibroblasts, suggesting the presence of “big conductance Ca2+-activated K+ (BKCa)” channels. The open probability of BKCa was significantly lower in AF than in SR fibroblasts. When cultured in the presence of paxilline, the shape of fibroblasts became wider and less spindle-like. Our data confirm previous findings on cardiac fibroblast electrophysiology and extend them by illustrating differential channel expression in human atrial fibroblasts from SR and AF tissue.